Critical Assessment of Estimation Procedures for Floor Acceleration Demands in Steel Moment-Resisting Frames - González, Isaac; Silva, António; Macedo, Luís; Monteiro, Ricardo; Castro, José Miguel (Frontiers in Built Environment, 2019)
Performance-based earthquake engineering has created the need for practical ways to assess the response of non-structural components (NSCs), which may be affected by deformation and/or acceleration demands of the superstructure. In the research study detailed in this paper, peak floor accelerations (PFAs) and floor response spectra (FRS) are computed using non-linear time history analysis (NTHA) for a comprehensive suite of 30 steel moment-resisting frame (MRF) archetypes, designed in accordance to Eurocode 8, considering different levels of non-linear seismic demand. The mean trends observed were compared with the most recent approaches proposed in the literature for prediction of acceleration demands. It was found that for PFAs, the available methods provide accurate predictions of the actual structural response under elastic and inelastic demands. However, the estimation procedures for the FRS yielded relevant differences in comparison to the observed elastic and inelastic responses, which entails the need for further development of such methods. It was also concluded that the existing PFA and FRS estimation methodologies present in several guidelines for seismic design and/or assessment do not provide reliable estimates of the acceleration demands incurred by the building. This highlights the very important need for an improvement of these codified procedures for a more reliable prediction of the seismic structural response.